Crack front segmentation under combined mode I- and mode IIIloading (Fracture and Structural Integrity, 2016)
This article approaches the topic of crack initiation and crack growth behaviour under combined mode I- and mode III-loading conditions. Such loading combinations especially lead to a crack, which unscrew out of its initial orientation and segments into many single cracks respectively facets. This characteristic depicts the crucial difference to a crack growth under pure mode I-loading, pure in-plane shearing (mode II) as well as 2D-mixed-mode-loadings. Since this stepped fractured surfaces thus far are proved little and therefore their characterisation remains to be done, a facets quantification using some characteristic dimensions will be performed within this article. After the description of experiments for facet creation the facet’s quantification using the crack profile near the initial position each facet will be analysed concerning characteristic dimensions. Finally the findings will be illustrated and discussed in this contribution.
Keywords: 3D-mixed-mode; Facets; Fatigue; Fracture; CTSR-specimen